HUBUNGAN MINAT MASUK PERGURUAN TINGGI DENGAN PRESTASI BELAJAR MAHASISWA DI JURUSAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Fatma, Siti; Elida, Elida; Chair, Ira Meirina (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
The purpose of research is to analyze the relationship between interest in going to college with the achievement of students in the department of Home Economic Faculty of Engineering State University of Padang. This study is a descriptive correlational study. The population numbered 844 people (S1 and D3) Food and Fashion, D4 Beauty, D4 Hospitality. Informant selection techniques in the study using purposive random sampling technique for 211 people. Data collection techniques with a structured questionnaire based on Likert scale that has been tested for validity and reliability. Based on the survey results revealed the percentage of incoming college student Interests overall categorized as low (29%), achievement of students in subjects categorized department of Home Economic overall quite satisfactory (52.1%). The results showed that there is a Positive and significant relationship between interest in going to college with the achievement of students in the department of Home Economic Faculty of Engineering State University of Padang. It means that the higher the interest the achievement of students is also good. Â Keywords: Interest and Achievement.